Dense ultra-thin copper foil with adhesion layer and preparation method thereof

The structure of large and small grain stacking in ultra-thin copper foil is formed through acid-base alternating electrodeposition technology, which solves the problem that ultra-thin copper foil is prone to pinholes in the prior art, improves its mechanical strength and electrical properties, and ensures the stability of grain size.

CN119753767APending Publication Date: 2025-04-04JIUJIANG TELFORD ELECTRONICS MATERIAL CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411740185.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing ultra-thin copper foils are prone to pinhole problems during the manufacturing process, which affects their mechanical strength and electrical properties. The prior art has limitations in solving this problem, especially when pinholes may reappear after high temperature treatment.

Method used

By adopting alternating acid-base electrodeposition technology, a large and small grain stacking structure is formed at the cross-section of ultra-thin copper foil, which improves grain boundary density and grain boundary energy, thereby ensuring grain size stability and reducing the generation of pinholes even after high temperature treatment.

Benefits of technology

The denseness of ultra-thin copper foil is achieved, its mechanical strength and electrical properties are improved, the stability of grain size is ensured, and the problem of pinholes after high temperature treatment is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753767A_ABST
    Figure CN119753767A_ABST
Patent Text Reader

Abstract

The present invention relates to a dense ultra-thin copper foil with an adhesion layer and a preparation method thereof, wherein the copper foil comprises an adhesion layer, an isolation layer and an ultra-thin copper foil; the cross-sectional crystal grains of the ultra-thin copper foil present a stacked form of large and small crystal grains. The cross-sectional crystal grains of the ultra-thin copper layer in the copper foil of the present invention present a stacked form of large and small crystal grains, large crystal grains constitute the main body of the copper foil, and small crystal grains are filled therein, so that the copper layer is dense, the pinhole problem of the pinhole ultra-thin copper foil is improved, thereby improving the mechanical strength and electrical properties of the copper foil, and being beneficial to improving the quality and reliability of electronic products; the doping of large and small crystal grains in the cross-sectional area of ​​the ultra-thin copper foil improves the grain boundary density and grain boundary energy, the copper foil has a small performance difference before and after downstream processing, the grain size and performance are stable, and the grain size changes little even after high-temperature treatment, which fundamentally solves the problem of grain size stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper foil manufacturing, and particularly relates to a dense ultra-thin copper foil with an adhesion layer and a preparation method thereof. Background Art

[0002] In modern electronic devices, ultra-thin copper foil is widely used in the manufacture of electronic products such as printed circuit boards (PCBs), flexible circuit boards (FPCs), and liquid crystal displays (LCDs) due to its excellent conductivity and processability. However, during the manufacturing process, ultra-thin copper foil often faces the problem of pinholes, that is, tiny holes appear on the surface or inside the copper foil, which not only affects the mechanical strength and electrical properties of the copper foil, but may also cause failures in electronic devices.

[0003] Existing technologies generally only use additives to change the density of copper foil during electrodeposition to improve the pinhole problem of ultra-thin copper foil. These additives affect the wettability of copper and electrolyte by inhibiting the bubble nucleation process in the plating solution or reducing the surface tension of the copper foil and liquid interface, making the copper foil appear delicate, uniform, and bright, thereby reducing the generation of pinholes. In addition, there are some technologies that control the growth of copper crystals by optimizing the parameters of the electroplating process, such as current density, temperature, pH value, etc., thereby reducing the generation of pinholes.

[0004] Although the existing technology can improve the pinhole problem of ultra-thin copper foil to a certain extent, there are still some problems and limitations. First, the use of additives may increase the complexity of the electroplating solution, and strict process control is required to ensure the uniform distribution and effectiveness of the additives. This not only increases production costs, but may also cause environmental pollution problems. Secondly, the copper foils produced by the existing technology are all formed by one-time electrodeposition in an acidic electroplating solution or an alkaline electroplating solution. Even if additives are added to the corresponding electroplating solution or the process parameters are optimized, it is still possible that in some cases, such as after high-temperature treatment, the pinhole problem will reappear due to unstable changes in the grain structure. Therefore, the existing technology still has certain limitations in solving the pinhole problem of ultra-thin copper foil. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a dense ultra-thin copper foil with an adhesion layer and a preparation method thereof. The cross-section grains of the ultra-thin copper layer in the copper foil present a stacked morphology of large and small grains, which improves the grain boundary density and grain boundary energy. Even after high-temperature treatment, the grain size changes little, fundamentally solving the problem of grain size stability.

[0006] The invention provides a dense ultra-thin copper foil with an adhesion layer, wherein the copper foil comprises an adhesion layer, an isolation layer and an ultra-thin copper foil; the cross-section crystal grains of the ultra-thin copper foil present a morphology of large and small crystal grains stacked.

[0007] Preferably, the adhesion layer is an adhesion copper layer.

[0008] Preferably, the isolation layer is selected from one or more of selenium-containing organic compounds, triazole-containing organic compounds, and amino-containing organic compounds.

[0009] Preferably, the ultra-thin copper foil has a thickness of 1.5-5 μm, a cross section of which is a stacked structure of large and small grains, and a maximum Feret diameter of 0.4-3.0 μm.

[0010] Preferably, the stacked morphology of large and small grains is obtained by alternately electrodepositing an acidic electrolyte and an alkaline electrolyte.

[0011] The present invention also provides a method for preparing a dense ultra-thin copper foil with an adhesion layer, comprising the following steps:

[0012] (1) preparing an adhesion layer by an electrolytic device, and then preparing an isolation layer on the surface of the adhesion layer;

[0013] (2) using an acid-base alternating electroplating process to electro-deposit an ultra-thin copper layer on the surface of the isolation layer;

[0014] (3) After the ultra-thin copper foil is electroplated, the copper foil is taken out and cleaned, and then the outer surface of the copper foil is roughened and cured, and finally chemically resistant, to obtain a dense ultra-thin copper foil with an adhesion layer.

[0015] Preferably, the acid plating solution used in the acid-base alternating electroplating process in step (2) comprises copper sulfate, sulfuric acid and deionized water, wherein the concentration of copper sulfate is 40-60 g / L, and the concentration of sulfuric acid is 80-100 g / L; the alkaline plating solution used comprises copper chloride, sodium hydroxide and deionized water, wherein the concentration of copper chloride is 40-60 g / L, and the concentration of sodium hydroxide is 50-60 g / L.

[0016] Preferably, the temperature of the acid plating solution in step (2) is 40-50°C, and the current density is 10-20A / dm 2 , the plating time is 30-60s; the temperature of the alkaline plating solution is 50-60℃, and the current density is 10-20A / dm 2 , the electroplating time is 30-60s.

[0017] There is no clear order of acid plating and alkali plating. It can be acid-alkali-acid or alkali-acid-alkali. No matter how many times the electroplating is alternated, there must be an ABA cycle.

[0018] Preferably, the chemical resistance treatment in step (3) includes dissimilar metal electroplating and organosilane adhesion.

[0019] The processes for preparing the adhesion layer and the isolation layer are conventional processes, and the processes for roughening and curing treatment and chemical resistance treatment are also conventional processes.

[0020] The grains in the cross section of the copper foil presented by the acid-base alternating electrodeposition technology adopted by the present invention will be in a state of large grains and small grains stacked, and this stacked state can be compared to the relationship between steel bars and concrete. Large grains are similar to steel bars as the overall skeleton, and small grains are similar to cement that can fill the gaps between grains. This state of large and small stacking is conducive to filling the gaps between grain boundaries, reducing pinholes in the electroplating process, and making the ultra-thin copper foil more compact. Not only that, the state of large grains and small grains stacking can increase the grain boundary density and grain boundary energy. Even after high-temperature treatment, the grains are not easy to nucleate and grow again due to the constraints of grain boundary energy. Therefore, the grain size in the copper foil also changes less, which can solve the pinhole problem caused by the change of crystal structure after high-temperature treatment of the copper foil.

[0021] Beneficial Effects

[0022] The grains in the cross section of the ultra-thin copper layer in the copper foil of the present invention are in the form of stacked large and small grains. The large grains constitute the main body of the copper foil, and the small grains are filled therein, so that the copper layer is dense, and the pinhole problem of the pinhole ultra-thin copper foil is improved, thereby improving the mechanical strength and electrical properties of the copper foil, which is beneficial to improving the quality and reliability of electronic products; the doping of large and small grains in the cross section of the ultra-thin copper foil increases the grain boundary density and grain boundary energy, the copper foil has little performance difference before and after downstream processing, the grain size and performance are stable, and the grain size changes little even after high-temperature treatment, which fundamentally solves the problem of grain size stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 Schematic diagram of the structure of the copper foil of the present invention; wherein 1 is an adhesion layer; 2 is an isolation layer; and 3 is an ultra-thin copper foil.

[0024] Figure 2 The cross-sectional grain structure diagrams of the ultra-thin copper foils prepared in Example 1 (a), Comparative Example 1 (b), and Comparative Example 2 (c). DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0026] Example 1

[0027] Figure 1The cross-sectional structure of the copper foil manufactured in this embodiment. The overall manufacturing process is the preparation of the adhesion layer, the electroplating of the isolation layer, the deposition of the ultra-thin copper layer, and the surface treatment, and finally the dense ultra-thin copper foil with the adhesion layer is obtained. The detailed preparation process of the double-layer copper foil of the present invention will be described below according to the production sequence.

[0028] First, the attached copper layer is prepared by electrolysis equipment. Since the ultra-thin copper foil is usually 1.5-5μm, normal equipment cannot directly drive the ultra-thin copper foil to move forward continuously through the transmission shaft with tension, so it is necessary to first make the attached copper layer, deposit the ultra-thin copper foil on the attached copper layer, and then peel off the ultra-thin copper foil when using it. The electrolyte of the attached copper layer is a copper sulfate solution, which contains sulfuric acid and Cu at a concentration of 110g / L. 2+ The ion concentration of H2SO4·5H2O is 97g / L. In an electrolyte at 50°C, the current is 40A / dm 2 Electrolysis was carried out for 45 seconds at a current density of 1.50 Å to obtain an attached copper layer with a thickness of 18 μm.

[0029] After the attached copper layer is prepared, an isolation layer that can separate the attached copper layer from the ultra-thin copper layer needs to be prepared. The attached copper layer is introduced into an organic solution containing 4-amino-1,2,4-triazole and immersed in it. The concentration of 4-amino-1,2,4-triazole is 3.6 g / L, and the immersion time is 40 seconds. After the immersion is completed, it is dried in an oven to remove impurities and residual foreign matter on the surface.

[0030] After the isolation layer is prepared, an acid-base alternating electroplating process is used to electro-deposit an ultra-thin copper layer on the surface of the isolation layer. The components of the acid plating solution include copper sulfate, sulfuric acid and deionized water, wherein the concentration of copper sulfate is 40g / L, and the concentration of sulfuric acid is 80g / L. The components of the alkaline plating solution include copper chloride, sodium hydroxide and deionized water, wherein the concentration of copper pyrophosphate is 45g / L, and the concentration of potassium pyrophosphate is 50g / L. The electrodeposition of acid-base alternating electroplating is carried out according to the steps of alkaline plating-acid plating-alkaline plating. The temperature of the acid plating solution is 45°C, and the current density is 15A / dm 2 The plating time is 40s. The temperature of the alkaline plating solution is 55°C and the current density is 15A / dm 2 , the electroplating time is 40s. The final ultra-thin copper layer thickness is 3μm.

[0031] After the ultra-thin copper foil is electroplated, take out the copper foil and spray and clean it with deionized water and anhydrous ethanol in turn, soaking or washing away the acid plating or alkaline plating electrolyte residue on the surface.

[0032] After the ultra-thin copper foil body is electroplated, a roughening treatment layer needs to be formed on the outer surface to ensure that the ultra-thin copper foil is tightly bonded to the prepreg when in use. The roughening treatment process is divided into roughening treatment and curing treatment. The roughening treatment uses sulfuric acid with a concentration of 110g / L and Cu 2+The copper foil is introduced into the copper sulfate electrolyte at 14A / dm 2 The copper foil was then electroplated at an average current density of 90 g / L and Cu 2+ Solidification electroplating was carried out in a copper sulfate solution with an ion concentration of 45g / L and an electroplating current density of 12A / dm 2 , electroplating time 12s.

[0033] After the roughening treatment is completed, the copper foil needs to be treated with chemical resistance to ensure the stability of the copper foil under long-term storage and extend the shelf life of the copper foil. The chemical resistance treatment is the electroplating of dissimilar metals and the attachment of organic silane. The main components of the electroplating solution are cobalt sulfate with a concentration of 1.1g / L, which also contains 20g / L boric acid and 10g / L sodium chloride solution. At 1.5A / dm 2 Electroplating at a current density of 12s obtains a chemically resistant dissimilar metal coating. The foil is then introduced into a solution containing 0.1wt% 3-(2,3-epoxypropyloxy)propylmethyldiethoxysilane for 12s to allow the silane to physically adsorb on the surface. It is then placed in a forced air oven and dried at 120°C for 10s to allow the silane on the copper foil surface to form a dense film layer and remove water stains on the surface.

[0034] Through the above steps, a dense ultra-thin copper foil with an adhesion layer can be obtained. At room temperature, the ultra-thin copper foil is separated from the adhesion layer, and the ultra-thin copper foil is observed under a 101-lumen dark box without light transmission points and pinholes. After heating at a high temperature of 250°C for 1 hour, it is placed in a 101-lumen dark box for observation and still has no light transmission points and pinholes. The ultra-thin copper foil cross-section slice test was measured by the Oxford EBSD probe, and the minimum value of the maximum Feret diameter is: 1.0μm, and the maximum value is 3.7μm. The cross-sectional grain structure is as follows Figure 2 shown.

[0035] Example 2

[0036] The differences between this embodiment and embodiment 1 are that (1) the thickness of the ultra-thin copper foil is adjusted to 1 μm; (2) the electrodeposition sequence of the ultra-thin copper layer is adjusted to acid plating-alkali plating-acid plating; and (3) the organic substance in the isolation layer is changed to L-selenium-methylselenocysteine.

[0037] At room temperature, the ultra-thin copper foil is separated from the adhesive layer. The ultra-thin copper foil is observed under a 101-lumen dark box without light transmission points or pinholes. After being heated at 250°C for 1 hour, it is still observed under a 101-lumen dark box without light transmission points or pinholes. The ultra-thin copper foil cross-section slice test was measured by the Oxford EBSD probe, and the minimum value of the maximum Feret diameter was: 0.9μm, and the maximum value was 3.2μm.

[0038] Example 3

[0039] The differences between this embodiment and embodiment 1 are that (1) the thickness of the ultra-thin copper foil is adjusted to 5 μm; (2) the electrodeposition sequence of the ultra-thin copper layer is adjusted to alkaline plating-acid plating-alkaline plating-acid plating; and (3) the organic substance in the isolation layer is changed to ethyl formate.

[0040] At room temperature, the ultra-thin copper foil is separated from the adhesive layer. The ultra-thin copper foil is observed under a 101-lumen dark box with no light transmission points or pinholes. After being heated at 250°C for 1 hour, it is still observed under a 101-lumen dark box with no light transmission points or pinholes. The ultra-thin copper foil cross-section slice test was measured by the Oxford EBSD probe, and the minimum value of the maximum Feret diameter is: 0.4μm, and the maximum value is 2.8μm.

[0041] Example 4

[0042] The difference between this embodiment and embodiment 1 is that (1) the ultra-thin copper layer electrodeposition sequence is adjusted to acid plating-alkali plating-acid plating-alkali plating;

[0043] At room temperature, the ultra-thin copper foil is separated from the adhesive layer. The ultra-thin copper foil is observed under a 101-lumen dark box without light transmission points or pinholes. After being heated at 250°C for 1 hour, it is still observed under a 101-lumen dark box without light transmission points or pinholes. The ultra-thin copper foil cross-section slice test was measured by the Oxford EBSD probe, and the minimum value of the maximum Feret diameter is: 0.9μm, and the maximum value is 3.0μm.

[0044] Comparative Example 1

[0045] The difference between this embodiment and embodiment 1 is that the ultra-thin copper layer electrodeposition step is adjusted and only acid plating is used instead.

[0046] At room temperature, the ultra-thin copper foil is separated from the adhesive layer. The ultra-thin copper foil is observed in a 101-lumen dark box without light transmission points or pinholes. After being heated at 250°C for 1 hour, it is placed in a 101-lumen dark box and observed to have light transmission points. The number of light transmission points is about 10 / dm 2 The average diameter of the light-transmitting spot is 2.6μm. The ultra-thin copper foil cross-section slice test was measured by the Oxford EBSD probe. The minimum value of the maximum Feret diameter is 0.6μm and the maximum value is 2.4μm.

[0047] Comparative Example 2

[0048] The difference between this embodiment and embodiment 1 is that the ultra-thin copper layer electrodeposition step is adjusted and only alkaline plating is used instead.

[0049] At room temperature, the ultra-thin copper foil is separated from the adhesive layer. The ultra-thin copper foil is observed under a 101-lumen dark box and there are light-transmitting spots. The number of light-transmitting spots is about 25 / dm 2The average diameter of the light-transmitting spots is 3.0 μm. After heating at 250°C for 1 hour, the light-transmitting spots were observed under a 101-lumen dark box. The number of light-transmitting spots was about 50 / dm 2 The diameter of the light-transmitting spot is about 3.5μm. The ultra-thin copper foil cross-section slice test was measured by the Oxford EBSD probe. The minimum value of the maximum Feret diameter is 1.4μm and the maximum value is 3.7μm.

Claims

1. A dense ultra-thin copper foil with an adhesive layer, characterized in that: The copper foil comprises an adhesion layer, an isolation layer and an ultra-thin copper foil; the cross-section crystal grains of the ultra-thin copper foil present a morphology of large and small crystal grains stacked.

2. The dense ultra-thin copper foil according to claim 1, characterized in that: The adhesion layer is an adhesion copper layer.

3. The dense ultra-thin copper foil according to claim 1, characterized in that: The isolation layer is selected from one or more of selenium-containing organic compounds, triazole-containing organic compounds, and amino-containing organic compounds.

4. The dense ultra-thin copper foil according to claim 1, characterized in that: The ultra-thin copper foil has a thickness of 1.5-5 μm.

5. The dense ultra-thin copper foil according to claim 1, characterized in that: The stacked morphology of large and small grains is obtained by alternately electrodepositing acidic electrolyte and alkaline electrolyte.

6. A method for preparing a dense ultra-thin copper foil with an adhesion layer, comprising the following steps: (1) preparing an adhesion layer by an electrolytic device, and then preparing an isolation layer on the surface of the adhesion layer; (2) using an acid-base alternating electroplating process to electro-deposit an ultra-thin copper layer on the surface of the isolation layer; (3) After the ultra-thin copper foil is electroplated, the copper foil is taken out and cleaned, and then the outer surface of the copper foil is roughened and cured, and finally chemically resistant, to obtain a dense ultra-thin copper foil with an adhesion layer.

7. The preparation method according to claim 6, characterized in that: The acid plating solution used in the acid-base alternating electroplating process in step (2) comprises copper sulfate, sulfuric acid and deionized water, wherein the concentration of copper sulfate is 40-60 g / L, and the concentration of sulfuric acid is 80-100 g / L; the alkaline plating solution used comprises copper chloride, sodium hydroxide and deionized water, wherein the concentration of copper chloride is 40-60 g / L, and the concentration of sodium hydroxide is 50-60 g / L.

8. The preparation method according to claim 7, characterized in that: The temperature of the acid plating solution in step (2) is 40-50°C, and the current density is 10-20A / dm 2 , the plating time is 30-60s; the temperature of the alkaline plating solution is 50-60℃, and the current density is 10-20A / dm 2 , the electroplating time is 30-60s.

9. The preparation method according to claim 6, characterized in that: The chemical resistance treatment in step (3) includes dissimilar metal electroplating and organosilane adhesion.

Citation Information

Cited By

  • Carrier copper foil and preparation method thereof, and preparation method of copper-clad plate and printed circuit board

    CN121038112A

  • Carrier copper foil, method for manufacturing the same, and method for manufacturing copper-clad plate and printed circuit board

    CN121038112B